2015
DOI: 10.1371/journal.pone.0144327
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Approach to Examining Conversational Dynamics between People with Dementia and Their Carers

Abstract: The progressive neuropathology involved in dementia frequently causes a gradual decline in communication skills. Communication partners who are unaware of the specific communication problems faced by people with dementia (PWD) can inadvertently challenge their conversation partner, leading to distress and a reduced flow of information between speakers. Previous research has produced an extensive literature base recommending strategies to facilitate conversational engagement in dementia. However, empirical evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Speech data used in experiments varied from being highly structured memory and reading tests [29,28,30], to organic, open-ended, conversation-like interactions (e.g. sharing stories) [31,27].…”
Section: Introductionmentioning
confidence: 99%
“…Speech data used in experiments varied from being highly structured memory and reading tests [29,28,30], to organic, open-ended, conversation-like interactions (e.g. sharing stories) [31,27].…”
Section: Introductionmentioning
confidence: 99%
“…Future research could therefore use qualitative content and discourse analysis techniques (e.g., Atay et al, 2015 ) to examine the themes that emerge from situational strength-related written and verbal messages received by employees from various organizational sources. Future research could also assess perceptions of situational strength from additional sources (e.g., non-social sources such as the nature of the work itself, Meyer et al, 2009 ; external social sources such as clients/customers, Oliver et al, 2016 ) as well as perceptions relevant to additional facets of situational strength not included in the current study (e.g., consistency and consequences, Meyer et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In effective interactions, the caregiver tends to align the conceptual content of his or her utterances to those of the patient, and these interactions are typically characterized by a strong leader-follower relation. It has also been shown that Discursis can be used to quantify content engagement between individuals with dementia and their caretakers, and that metrics associated with short-term topic repetition are related to subsets of communicative interactions manually coded as Bactive listening^ (Atay et al, 2015). These relations show the potential of CRA metrics in the systematic evaluation of communicative content.…”
Section: Conceptual Recurrence Analysismentioning
confidence: 99%
“…Despite this potential limitation, we believe our results successfully demonstrate both the experimental utility of the proposed novel CRA metrics and how they may be affected by parameter choices. We also note that CRA is a relatively new tool, and some of the metrics derived from it require further research before they can be clearly interpreted (though some work along these lines has been recently conducted; e.g., Atay et al, 2015). Furthermore, a variety of parameter values must be set during data analysis with CRA, including the number of key terms and the source of key terms.…”
Section: Selected Key Conceptsmentioning
confidence: 99%